The Efficacy Of The Virtual: From Che As Sign To Che As Agent - Cambre, Carolina (Public Journal of Semiotics, 2012)
This paper begins by tracing a path through salient developments in semiotic theory regarding the visual. It examines the political functions of cultural and discursive semiotic systems through which graphic images and gestures are appraised, interpreted and given significance: it is not about what they mean, but rather how they construct meanings and how such meanings accrue importance. I consider the simultaneous material and social nature of both vision and representation. My primary focus is with the visual and social performance of the image of Che Guevara as derived from Alberto Korda’s famous 1960 photograph, El Guerrillero Heroico. Using this image as a heuristic in the case of Che Guevara’s image in East Timor during the time of Indonesia’s dictatorship and independence struggle, I will outline how the performative aspect creates a space of “ethical possibility” through visualizations. I will tease out anthropologist Alfred Gell’s (1997) radical notions of the agency of art and explore the possibilities of Donald Preziosi’s (2003) elaboration of Roman Jakobson’s addition of a fourth sign type, namely artifice. The inclusion of artifice is underwritten by an understanding of A. J. Greimas’(1987) semiotic square as a way to introduce complexity into binary or dual forms. I posit the square is as a dynamic, fractal-like construction. Building on this foundation, I articulate possible connections between artifice and the notion of the virtual as described by a philosophers and academicians from C.S. Peirce to Rob Shields, as a contribution to this theorizing and explore its relevance to the Che image phenomenon. Overall, it is the desire to find ways to speak about the Guerrillero Heroico’s social and political activity and resonance that drives the theoretical contributions in this piece.